Singular integrals and sublinear operators on amalgam spaces and Hardy-amalgam spaces - Ho, Kwok-Pun (MATHEMATICA SCANDINAVICA, 2021)
In this paper, we establish the extrapolation theory for the amalgam spaces and the Hardy-amalgam spaces. By using the extrapolation theory, we obtain the mapping properties for the Calderón-Zygmund operators and its commutator, the Carleson operators and establish the Rubio de Francia inequalities for Littlewood-Paley functions of arbitrary intervals to the amalgam spaces. We also obtain the boundedness of the Calderón-Zygmund operators and the intrinsic square function on the Hardy-amalgam spaces.